Fatigue resistance of thigh muscles in sport games players - Pontaga, I.; Zidens, J. (Archives of Budo Conference Proceedings, 2015)
Background and Study Aim. Changed thigh muscles action balance can cause sports injuries. The aim of our investigation was the knowledge about effect of thigh muscles fatigue resistance on the knee flexor (Fl)/ extensor (Ext) muscles mean work (W) and power (P) ratio. Material and Methods. Fourteen amateur male handball players participated The tests were carried out by a dynamometer system using the knee isokinetic flexion-extension movements at angular velocity of 90°/s (five repetitions) and 240°/s (20 repetitions) by the concentric contractions. The mean thigh muscles W, P and Fl/Ext muscles mean W and P ratios were calculated for the first ten and last ten repetitions. The correlation between the thigh muscles peak torques (tmax) at the velocity of 90°/s, 240°/s and W, P at the first and last ten repetitions was determined. Results. Mean W produced by the knee Fl in the last ten movements was smaller than in the first ten motions (p<0.02). The knee WFl/WExt=0.69; PFl/PExt=0.65 in the last ten motions were lower than in the first ten movements: WFl/WExt=0.73; PFl/PExt=0.71 (p<0.002). Therefore the knee joint trauma may occur more probably after fatigue appearance. The positive correlation between thigh muscles tmax and W, P in the first ten and last ten knee movements (p<0.01) confirms that strength training of muscles will improve not only the maximal strength but also the fatigue resistance. Conclusion. The significant positive correlation between thigh (hamstrings and quadriceps femoris) muscles peak torques and the mean work and power of the same muscles in the first ten and last ten knee flexion-extension movements (p<0.01) confirms that the strength training of these muscle groups will improve not only the maximal strength but also the fatigue resistance of these muscles.